Interplay between the dividing Cell and its neighbors regulates adherens junction formation during cytokinesis in epithelial tissue - Herszterg, Sophie; Leibfried, Andrea; Bosveld, Floris; Martin, Charlotte; Bellaïche, Yohanns (Developmental cell, 2023)
How adherens junctions (AJs) are formed upon cell division is largely unexplored. Here, we found that AJ formation is coordinated with cytokinesis and relies on an interplay between the dividing cell and its neighbors. During contraction of the cytokinetic ring, the neighboring cells locally accumulate Myosin II and produce the cortical tension necessary to set the initial geometry of the daughter cell interface. However, the neighboring cell membranes impede AJ formation. Upon midbody formation and concomitantly to neighboring cell withdrawal, Arp2/3-dependent actin polymerization oriented by the midbody maintains AJ geometry and regulates AJ final length and the epithelial cell arrangement upon division. We propose that cytokinesis in epithelia is a multicellular process, whereby the cooperative actions of the dividing cell and its neighbors define a two-tiered mechanism that spatially and temporally controls AJ formation while maintaining tissue cohesiveness.